Bailey's Industrial Oil and Fat Products 2005
DOI: 10.1002/047167849x.bio037
|View full text |Cite
|
Sign up to set email alerts
|

Butter

Abstract: Butter is one of the oldest forms of preserving fat components of milk. Its manufacture dates back to some of the earliest historical records. The evolution of the art of buttermaking has been associated with the development and use of equipment. The construction of creaming and buttermaking equipment in the eighteenth century led to the appearance of the barrel churn. Creaming was at first done by a method called shallow pan. This was followed by a deep‐setting system. This shortened process time an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…A study of Kristensen et al [59] reported that a very high storage temperature resulted in a darker butter color. Differences in butter color result from variation in the color of butter fat, variation in the size of fat globules, the presence or absence of salt, the condition of working the butter [60], the type of packaging, and storage temperature. The color of dairy products also depends on the type and amount of coloring added.…”
Section: Source Of Milkmentioning
confidence: 99%
“…A study of Kristensen et al [59] reported that a very high storage temperature resulted in a darker butter color. Differences in butter color result from variation in the color of butter fat, variation in the size of fat globules, the presence or absence of salt, the condition of working the butter [60], the type of packaging, and storage temperature. The color of dairy products also depends on the type and amount of coloring added.…”
Section: Source Of Milkmentioning
confidence: 99%